FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN IBU DALAM PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) DI RT 02 RW 03 KELURAHAN PINANG KENCANA KOTA TANJUNG PINANG - Sumanti, Yulia; Susanti, Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Cervical cancer is a malignancy that occurs and comes from cervical cells. TheÂ  cervical cancer is caused by infection Human Papilloma Virus (HPV) / papilloma virus in humans. Cervical cancer is the most common cancer in women with an estimated 570,000 new cases in 2018 representing 6.6% of all female cancers. About 90% of deaths caused by cervical cancer occur in low and middle income countries, including Indonesia. This research is an analytic study using cross sectional method. The sample in this study was WUS in RT 02 RW 03 Kelurahan Pinang KencanaÂ  Tanjung Pinang City. Sampling with a purposive sampling technique obtained a total sample of 83 women. Data were analyzed using the Chi-Square test with Î± 0.05, with the results indicating no relationship between knowledge and IVA examination with results P = 0.19> Î± 0.05. There is no relationship between attitude and IVA examination with P = 0.34> Î± 0.05. And there is no relationship between Access of Information with IVA Examination with the results of P = 0.175 <Î± 0.05. This research is expected to improve health personnel in providing motivation, information and encouragement to health cadres, in order it can be an example for women of childbearing age in conducting IVA examination.